Asociación entre síntomas depresivos y ansiedad en pacientes adultos con diabetes mellitus tipo 2 de un hospital de Loreto, 2024 - Panduro García, Carlos Eduardo (2025)
Type 2 diabetes mellitus (T2DM) is a highly prevalent chronic disease associated not only with multiple physical complications but also with mental health disorders such as anxiety and depression. These psychological comorbidities can negatively affect metabolic control, treatment adherence, and the overall quality of life of patients. Objective: To determine the association between depressive and anxiety symptoms in adult patients with type 2 diabetes mellitus at a hospital in Loreto in 2024. Methods: An observational, analytical, and cross-sectional study was conducted with a sample of 142 patients diagnosed with T2DM. The PHQ-9 and GAD-7 instruments were used to assess depressive and anxiety symptoms, respectively. Sociodemographic and clinical variables were also collected using a structured data sheet. Statistical analysis included bivariate tests (Chi square, Mann-Whitney U) and multivariable logistic regression, considering a p-value < 0.05 as statistically significant. Results: All patients presented some level of depressive symptoms, with mild (43.7%) and moderate (31.7%) levels being the most common. The most frequent depressive symptoms were sleep disturbances (71.1%) and fatigue (63.3%), while the predominant anxiety symptoms were nervousness (56.7%) and excessive worry (55.6%). Regarding anxiety, the majority showed some degree, with moderate symptoms being the most prevalent (48.6%). A significant association was found between depressive symptoms and older age, duration of diagnosis over five years, and poor glycemic control (HbA1c > 7%). Anxiety symptoms were significantly associated with lower socioeconomic status and inadequate metabolic control. In the multivariable analysis, older adults were up to 12 times more likely to present depressive symptoms compared to younger adults, and those with more than 10 years since T2DM diagnosis had a ninefold higher probability of experiencing depression. Conclusions: There is a high burden of depressive and anxiety symptoms in patients with T2DM, mainly associated with clinical factors such as poor glycemic control and longer disease duration, as well as sociodemographic factors like age and socioeconomic status. These findings underscore the importance of implementing psychological assessment and intervention strategies as part of comprehensive care for diabetic patients, in order to optimize treatment outcomes and overall well-being.